Wild girl - Giff, Patricia Reilly (Wendy Lamb Books, 2009)
Lidie lives in Brazil where she's free to ride and be a wild girl, but when she turns twelve, she leaves Brazil for New York where her father and her older brother live. She proves herself as a strong, young girl when she becomes determined to ride Wild Girl, the filly her father has just purchased for his race track.